Tingkat Kesadaran Terhadap Pelaksanaan Zakat Profesi (Studi Kasus Universitas Ibn Khaldun Bogor) - Irma Lailan; Ikhwan Hamdani; Syarifah Gustiawati (IQTISHODUNA: Jurnal Ekonomi Islam, 2018)
Zakat profession it self is one of the themes of contemporary jurisprudence that has not been fully accepted among Islamic scholars. Some circles still doubt even reject the validity of the withdrawal of profession zakat imposed on various professions "wet" which results far above the farmers' income. But the supporters of zakat profession seem to be more powerful influence and its teachings proved in "Act No. 23 of 2011 on the management of zakat in Article 4 point h on income and services has been declared by the Act as one of the objects of zakat mal in Indonesia". This research uses quantitative method. Data collection techniques using questionnaires, while data analysis techniques using multiple linear regression analysis assisted SPSS program 16. This paper aims to determine the level of awareness of the implementation of professional zakat in the measure of variables such as the perception of zakat profession and other factors affecting the implementation of professional zakat . The results showed that perception, other factors together have positive and significant effect on the implementation of zakat profession and affect the level of kedasaran on the implementation of professional zakat.